Traceability System for Segmented Livestock Meat Processing based on Radio Frequency Identification Technology - Chai, Haojie; Wang, Yanyan (International Journal of Computer Science and Information Technology, 2024)
Based on radio frequency identification technology, this paper proposes a novel traceability system for the processing of segmented livestock meat, aiming to address the issues of information opacity and tracing difficulties in the existing processes. The system includes functions such as raw material tracing, processing monitoring, and product quality inspection and tracing. It employs a 32f103c8t6 microcontroller and an ESP8266 WiFi remote communication module to establish a connection with the host computer. Communication with the microcontroller is established through serial communication for data reception and transmission. The system also possesses product quality inspection and tracing capabilities, enabling the timely detection of potential quality issues. Testing and evaluation have confirmed that the system performs exceptionally well in practical applications, effectively enhancing processing efficiency and accuracy, reducing food safety risks, and enabling real-time updating and sharing of product information. By providing real-time tracking and monitoring of the processing process, the system enhances production efficiency and accuracy, ensuring food safety.